Mantodea (Insecta) of Uruguay: diversity and distribution - Trillo, Mariana C.; Agudelo, Antonio A.; Guerrero, José C.; Miguel, Lucía; Lorier, Estrellita (Zootaxa, 2021)
Praying mantises (Order Mantodea) are charismatic insects thanks to their diverse and peculiar appearance and surprising behaviors. However, studies on this order are scarce, particularly in the Southern Neotropical Region. Here we present the first catalogue of praying mantises from Uruguay. We revised Mantodea specimens deposited at Colección de Entomología, Facultad de Ciencias (FCE-MN), Universidad de la República, Montevideo, Uruguay. We recorded information about distribution and notes on the biology of the species. Nineteen species are reported for Uruguay, including new family, genera or species for the country. We report the presence of six taxa for first time: the family Mantoididae, genus Pseudovates, Musoniella and Metaphotina, the species Mantoida beieri, Eumusonia livida, Musoniella argentina, Metaphotina brevipennis, Parastagmatoptera theresopolitana and Pseudovates iheringi. We could confirm four species previously reported for the country, but eight species are based on dubious records or species and we cannot confirm their current occurrence in this work. More studies are needed in the country for further investigations of Mantodea in the country and the region.